Study of sand brick ratio 13 for partial replacement of sand with palm kernel shells (0%, 10% and 20%) - Maisarah, Abdullah (2017)
In this study, samples of sand brick that added with palm kernel shells (PKS) are produced to determine the best compressive strength of sand brick and to identify the best water absorption of sand brick with different percentages. There are 3 different percentages which are 0%, 10% and 20% will be replaced with the sand. The size of sand brick is 225mm x 113mm x 75mm. There are 120 bricks with three different percentage of ratio palm kernel shells are produced 20 samples for each percentage for 7 days and 28 days to get the average results of the compressive strength and water absorption. The outcome of these results is to compare the compressive strength and water absorption of sand brick are replaced with palm kernel shells and control samples. From the average of compressive strength by using air curing is decrease from 34.06 N/mm2 until 22.66 N/mm2 for 7 days and from 36.04 N/mm2 until 24.86 N/mm2 for 28 days while using water curing method also decrease from 33.00 N/mm2 until 22.32 N/mm2 for 7 days and from 34.63 N/mm2 until 23.52 N/mm2. Then, the average for water absorption by using air curing is increase from 2.41% until 5.35% for 7 days and from 2.64% until 6.33% for 28 days while by using water curing also increase from 2.67% until 6.24% for 7 days and from 2.94% until 6.63% for 28 days. This study will be useful to improve the strength of the sand brick by using smaller percentage from this study.